Thriving at work and perceived overqualification as predictors of employee career outcomes - Amira, Ghina; Febrianti, Adjeng Mariana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to understand the influence of thriving at work and perceived overqualification on employee career outcomes, which is seen from career satisfaction and turnover intention. This study is carried out on service company employees in Bandung, West Java. The sampling technique in this study is carried out by simple random sampling, with the final number of samples of 110 respondents. The data collection is done by distributing questionnaire using online platforms to the respondents. The questionnaire items used is measured using 5-point Likert scale. The data is then processed using multiple linear regression analysis with SPSS 23 software. The results of this study indicate that thriving at work positively influences employee career satisfaction, and negatively influences turnover intention. On the other hand, perceived overqualification negatively influences career satisfaction and positively influences turnover intention.